(untitled) (Journal of Media studies, 2023)
The article examines the influence of the state information orderon the content of regional periodicals. A number of topical issues are considered,such as the concept of "agenda", factors affecting the content of regionalnewspapers, discrepancy between materials and the real life of the region andthe needs of the population.The purpose of the study is to propose effective methods for activating the workof regional periodicals, studying the current situation on the example of localnewspapers. As part of the study, a content analysis of the Panfilov regionalnewspaper "Zharkent Ongiri" was carried out. Since the state information orderis an integral part of the Kazakhstan media, it is explained how much it affectsthe content of periodicals in the region, the coverage of current topics.